2019
DOI: 10.1111/let.12328
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of ventrally directed spiralia in a Permian spiriferellid brachiopod and implications for its feeding system

Abstract: Spiralia are lophophore‐supporting, coiled internal structures developed in some extinct brachiopods. In spite of considerable variations in their orientation, the spiralia of most spiriferide and spiriferinide taxa are known to be laterally directed. Recent studies have shown that these brachiopods consistently have a median inhalant and lateral exhalant feeding system. Here, we report a Permian spiriferellid brachiopod fossil (Spiriferella protodraschei) bearing ventrally directed spiralia in its interior. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…5.3, 5.6). Lee et al (2019a) recently reported ventrally directed spiralia in the Permian spiriferellide brachiopod Spiriferella protodraschei Lee and Shi in Lee et al, 2019b. Their reconstruction revealed that each spiralium in the specimen is almost uniform in diameter and does not show the apically tapering pattern, and they appear to have directly developed from strong and anteriorly extended crura. Based on the extraordinary orientation and form of the spiralia, the authors suggested that this species likely had developed a considerably modified feeding pattern similar to that of the living rhynchonellides.…”
Section: Journal Of Paleontology 95(3):553-567mentioning
confidence: 99%
See 1 more Smart Citation
“…5.3, 5.6). Lee et al (2019a) recently reported ventrally directed spiralia in the Permian spiriferellide brachiopod Spiriferella protodraschei Lee and Shi in Lee et al, 2019b. Their reconstruction revealed that each spiralium in the specimen is almost uniform in diameter and does not show the apically tapering pattern, and they appear to have directly developed from strong and anteriorly extended crura. Based on the extraordinary orientation and form of the spiralia, the authors suggested that this species likely had developed a considerably modified feeding pattern similar to that of the living rhynchonellides.…”
Section: Journal Of Paleontology 95(3):553-567mentioning
confidence: 99%
“…5.3, 5.6). Lee et al (2019a) recently reported ventrally directed spiralia in the Permian spiriferellide brachiopod Spiriferella protodraschei Lee and Shi in Lee et al, 2019b. Their reconstruction revealed that each spiralium in the specimen is almost uniform in diameter and does not show the apically tapering pattern, and they appear to have directly developed from strong and anteriorly extended crura.…”
Section: Journal Of Paleontology:1-15mentioning
confidence: 99%